Curative treatment incorporating subjective decisions on age and frailty is not beneficial for older patients with oral cavity squamous cell carcinoma - Alice Prevost; Hugo Poncet; Victor Benvegnu; Vinciane Poulet; Jacqueline Butterworth; Andréa Varazzani; Frédéric Lauwers; Franck Delanoë (PLoS ONE, 2025)
The curative surgical treatment of older patients with oral cavity squamous cell carcinoma (OCSCC) is often personalized by incorporating subjective decisions on age and frailty. We aimed to determine here whether real-world recommended treatment, following official French guidelines only, versus deviation from recommended treatment was beneficial for older patients with OCSCC. To do this, we performed a retrospective evaluation of patients >70 years managed for treatment of p16-negative OCSCC in our tertiary hospital center in France between 2007 and 2017. The association between postoperative morbidity and deviation from recommended treatment was analysed using multivariate logistic regression. Cox Proportional Hazards Regression assessed the associations between deviation from recommended treatment and both the hazard of recurrence and mortality within 5 years. We included 185 patients who were recommended surgical resection of OCSCC: n = 147/185 (79%) patients underwent the recommended treatment and 38/185 (21%) patients underwent deviation from recommended treatment. Patients who underwent deviation from recommended treatment had a significantly lower recurrence-free survival (p = 0.0005) and overall survival (p = 0.008). Deviation from recommended treatment was found independently associated with increased development of 3-month postoperative morbidity (adjusted odds ratio 2.63 [1.23–5.82]; p = 0.02) and increased risk of recurrence within 5 years (adjusted hazard ratio 1.79 [1.14–2.83]; p = 0.01). Deviation from recommended treatment was not found independently associated with increased risk of mortality within 5 years (1.35 [0.82–2.23]; p = 0.2). Overall, deviation from recommended treatment was associated with worse outcomes and so we have identified a decision-making process biased by undocumented and subjective evidence. Preoperative risk models therefore require further validation in older patients with OCSCC to define more appropriate treatment regimens.